ANALISIS PROSES BERPIKIR KRITIS MATEMATIKA SISWA PADA PEMBELAJARAN MODEL REALISTIC MATHEMATIC EDUCATION (RME) MATERI SPLDV DI KELAS X MAN 1 JEMBER: Bahasa Indonesia - Wahyuni, Indah; Fazri, Ahmad; Zuhro, Afkarina Khoiruz; Hasanah, Uswatun (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
Students must have the ability or potential as well as a good mathematical attitude, such as the ability to solve problem in solving problems in this Systems of Linear Equations in Two Variables material. These abilities include mathematical problems, including the abilities that exist within each student so that they can solve problems in the Systems of Linear Equations in Two Variables material. This research was conducted to find out how students solve and apply two-variable linear equation systems at the 10th-grade high school level in real-world problems. This research also examines real-world problems and students' systematic thinking on how students solve or apply mathematics problems in Systems of Linear Equations in Two Variables material. This data collection was carried out by examining class x level students at MAN 1 JEMBER with research themes that had been implemented. The application criteria used in this research use journal articles on Sinta 2 or Google Scholar which must be published within the last 5 years maximum. After all the data has been collected, the next step is the data processing process which is carried out by analyzing the data on the class x high school level learning model in real life. The purpose of this research is to determine the abilities of students with visual, auditory, and kinesthetic learning styles and to be able to conclude the application of how students solve mathematics problems in Systems of Linear Equations in Two Variables material.